Eye-tracking insights into cognitive strategies, learning styles, and academic outcomes of Turkish medicine students - Hande Argunsah; Levent Altıntaş; Melike Şahiner (BMC Medical Education)
Abstract Background Individual differences in learning preferences and cognitive strategies play a crucial role in shaping academic outcomes, emphasizing the need to customize educational approaches to meet diverse learner needs. This study explores the relationship between gaze behavior, learning style and academic performance in 20 sophomore Turkish medical students. Methods Eye-tracking metrics, gaze duration, fixation count, fixation duration, and saccadic movements, were recorded using Tobii Pro Glasses 2 eye tracker during Trail Making, Visual Sustained Attention and the Stroop Tests and associated with the Felder-Soloman learning style and academic performance. Results Eye-tracking data revealed consistent patterns across tasks, with fixation percentages averaging 94% and saccadic movements accounting for 6%, suggesting uniform attention allocation. Pupil diameter variation did not significantly differ between tasks, implying similar cognitive demands across all tasks. Most of the participants demonstrated moderate-to-strong visual learning preferences, particularly females. Significant gender differences were observed in learning preferences and academic performance, with higher Grade Point Averages among female participants with stronger visual learning preferences. Conclusions The study underscores gender-based differences in learning preferences and the alignment of these preferences with academic performance. The findings suggest the importance of tailoring educational strategies to support diverse learning needs, with a particular emphasis on visually engaging materials.